Correlation Analysis of Serum Vitamin D Levels and Postoperative Cognitive Disorder in Elderly Patients With Gastrointestinal Tumor - Jialei Zhang; Jialei Zhang; Xiaoling Zhang; Yongyan Yang; Jun Zhao; Yonghao Yu (Frontiers in Psychiatry, 2022)
PurposeVitamin D prevents hypocalcaemia, osteoporosis, and infections, among other problems, and is involved in the prevention and treatment of cardiovascular and neurological diseases. Recently, vitamin D was shown to improve cognitive dysfunction caused by Alzheimer's disease and vascular dementia. This study aims to explore the correlation between preoperative serum vitamin D and postoperative cognitive disorder (POCD) occurrence in elderly patients with gastrointestinal tumors to guide perioperative medication use and promote early patient recovery.MethodsThis study recruited 238 elderly patients (65 ≤ age ≤ 85) who underwent gastrointestinal tumor surgery; 117 cases were enrolled, and 55 controls of the same age and education level as the cases were included. Blood samples were taken preoperatively and at 7, 15, 30, and 90 days postoperatively, and plasma vitamin D (25OH-D3) and glutathione (GSH) was measured. Different from the previous diagnosis of POCD was obtained by telephone interview through Cognitive Status Modified Telephone Interview (TICS-m), mainly for memory impairment, a series of neuropsychological tests was used to evaluate cognitive function, Picture Recollect Test, Stroop Color-word Test, and Digit Symbol Substitution Test were used to comprehensively evaluate the three domains of cognitive function of patients, namely memory, attention and information processing ability. All neuropsychiatric assessments were performed at the bedside and completed face-to-face by the assessment staff and the patient.ResultsA total of 65.8% (77/117) of elderly patients undergoing gastrointestinal tumor surgery had preoperative vitamin D deficiency (serum 25OH-D concentration < 12 ng/ml), of whom 46.7% (36/77, 7 days after surgery), 31.2% (24/77, 15 days after surgery), 15.6% (12/77, 30 days after surgery), and 9% (7/77, 90 days after surgery) of patients developed POCD; 7.5% (3/40) of patients without vitamin D deficiency developed PNDs, which was detected only on the 7th day after surgery.ConclusionsVitamin D deficiency can increase neurocognitive disorder risk in elderly patients during the perioperative period, possibly because low vitamin D levels cannot effectively inhibit the postoperative oxidative stress increase.Trial RegistrationThis experiment was approved and registered by the China Clinical Trial Registration Center, registration number ChiCTR2100046900 (30/05/2021).